FEASIBILITY LIVESTOCK OF BROILER (GALLUS DOMESTICUS) IN WADASLINTANG DISTRICT SUBDISTRICT WONOSOBO - Zulfanita,Uswatun Hasanah,Hanung Dhidhik Arifin (Tadulako University, 2015)
This study aims to determine : Feasibility of broiler farming in Wadaslintang District, the method basic was used in this research is survey method with the research location Wadaslintang District SubdistrictWonosobo. Sampling technic was used 43 farmers.Based on the results that broiler farming in Wadaslintang the needed total average cost is Rp8,927,929.77 average total revenue is Rp 20,653,290.70, the average income is Rp13,487,185.60, an average profit is Rp11,725,360.93. Rated R/C ratio is 2.31, productivity of capital π/C ratio is 131.33%, labor productivity Rp544.223,71/HKO, farmer income is Rp 13,487,185.60 > land rent value is Rp 1,353 per production period 488,37, meat chiken production > BEP value of meat chiken production1744.54 > 403.00, Income > BEP value of income is 20,653,290.70 >Rp4,759,218.42,meat prices>BEP prices Rp11.838,77 >Rp5.117,62, if the price decline is not exceed 56.78%, the farmers do not losses, its mean that broiler farming is feasible to grow up.